(untitled) (Veterinary Science, 2025)
The aim was set to determine the effect of the presence of Eimeria spp. in peripartum females on the parasitic infection rate in alpaca babies. The study was conducted at the Centro de Investigación de Camélidos Sud Americanos "La Raya" in Marangani, Cusco, Peru. The entirety of 168 alpaca samples were collected. These were divided into 5 groups: 1) n=30 prepartum females, 2) n=20 newly postpartum females, 3) n=30 mothers at 15-21 days postpartum, 4) n=30 mothers at 30-60 days postpartum, 5) n=30 babies from 15 to 21 days, and 6) n=28 babies from 30 to 60 days old. Coproparasitological test of flotation concentration and the modified McMaster technique were performed in the Veterinary Medicine Parasitology Laboratory of UNSAACSicuani. Data were analyzed using the chi-square test. As results, E. punoensis is identified as the predominant species in peripartum females, being present in up to 20% of newly postpartum alpacas. The number of females infected with Eimeria spp. remains stable during pre- and postpartum periods, showing no significant differences between peripartum female groups (p≥0.05). In contrast, 57.14% and 25% of the babies were infected with E. lamae and E. macusaniensis, respectively. Alpaca babies aged 30 to 60 days have been the most affected with pathogenic Eimeria (71.47%) in contrast to their mothers (p<0.05). It was concluded, that there was no clear relationship between the Eimeria species infecting mothers and their babies. The immunoperipartum effect in female alpacas against Eimeria spp. infection could not be demonstrated either.